The Effect of Education Through Video Media on the Knowledge of Postpartum Mothers about Perineal Wound Care - Safitri, Eka Ayuningtyas; Ma'rifah, Umi; Puspita, Irma Maya (Universitas Islam Lamongan, 2024)
Perineal wound care is an attempt to avoid perineal wound infection. Education through video media is aneducational tool that can make it easier for someone to receive information. The purpose of this study was todetermine the effect of education through video media on postpartum mothers' knowledge about perineal woundcare. The method used is Pre-Experimental Design, with the type of research one group pretest-posttest design.This research was conducted at TPMB Muarofah in January with a total sample of 55 respondents.The population of this study were all postpartum mothers who were included in the inclusion criteria using the Consecutivesampling technique. Data collection uses a questionnaire sheet. Data analysis used univariate analysis withfrequency distribution and bivariate analysis using the Wilcoxon Sign Rank test. The results of the univariateanalysis showed that of the 55 respondents before being given health education through video media, there were50 respondents who had less knowledge and after being given health education through video media, there were 48 respondents who had good knowledge. From the Wilcoxon Sign Rank test that was carried out, the results were <0.00, so it can be stated that health education through video media has an effect on the knowledge of postpartum mothers about perineal wound care at TPMB Muarofah, Surabaya City.